1980
DOI: 10.1128/jvi.34.1.142-153.1980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tunicamycin on herpes simplex virus glycoproteins and infectious virus production

Abstract: The antibiotic tunicamycin, which blocks the synthesis of glycoproteins, inhibited the production of infectious herpes simplex virus. In the presence of this drug, ['4C]glucosamine and [3H]mannose incorporation was reduced in infected cells, whereas total protein synthesis was not affected. Gel electrophoresis of [2-3H]mannose-labeled polypeptides failed to detect glycoprotein D or any of the other herpes simplex virus glycoproteins. By use of specific antisera we demonstrated that in the presence of tunicamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
87
0
1

Year Published

1983
1983
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 44 publications
14
87
0
1
Order By: Relevance
“…This may explain the lower density of the noninfectious virus particles produced by tunicamycin-treated cells. The influence of tunicamycin on infectivity indicated that glycosylation of the viral proteins is required for the production of infectious virus, a phenomenon previously reported for several other enveloped viruses (Schwartz et aL, 19'76, Morrison et aL, 19'78;Nakamura and Compans, 19'78;Stohrer and Hunter, 1979;Pizer et al, 1980). When GBK cells were treated with monensin, reduced amounts of infectious virus particles were produced.…”
Section: Effectsmentioning
confidence: 54%
See 1 more Smart Citation
“…This may explain the lower density of the noninfectious virus particles produced by tunicamycin-treated cells. The influence of tunicamycin on infectivity indicated that glycosylation of the viral proteins is required for the production of infectious virus, a phenomenon previously reported for several other enveloped viruses (Schwartz et aL, 19'76, Morrison et aL, 19'78;Nakamura and Compans, 19'78;Stohrer and Hunter, 1979;Pizer et al, 1980). When GBK cells were treated with monensin, reduced amounts of infectious virus particles were produced.…”
Section: Effectsmentioning
confidence: 54%
“…Tunicamycin, by acting as an analog of UDP-N-acetylglucosamine, interferes with the formation of the N-acetylglucosamine pyrophosphoryldolichol intermediate and thereby completely inhibits the synthesis of N-linked oligosaccharide side chains (Schwartz and Datema, 1980). Consequently, all glycoprotein-containing enveloped viruses are affected by tunicamycin in such a way that it prevents maturation and production of infectious virus (Schwartz et ai, 1976, Morrison et al, 1978Nakamura and Compans, 1978;Stohrer and Huner, 1979;Pizer et aL, 1980). Monensin is a carboxylic ionophore that is able to equilibrate Na+/K+ levels with a selectivity for Na+ (Pressman, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports that inhibitors N-glycosylation block production of infectious HSV. Thus, tunicamycin reduces the yield of infectious virus by a factor of 103 and 2deoxyglucose by a factor of about 102 (Pizer et al, 1980;K~tz et al, 1980K~tz et al, Courtney et al, 1973. Despite the dramatic decrease in infectious particles, the number of enveloped HSV particles is not significantly decreased, indicating production of morphologically intact enveloped particles without infectivity (Courtney et al, 1973;Pizer et al, 1980;Katz et al, 1980).…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…Cells infected with herpes simplex virus provide a useful system for investigating the processes discussed above. Previous studies have shown that glycoproteins specified by herpes simplex virus type 1 (HSVl) contain O-linked oligosaccharides (Oloffson et al, 1981) as well as N-linked oligosaccharides (Pizer et al, 1980;Serafini-Cessi and Campadelli-Fiume, 1981;Person et al, 1982;Wenske et al, 1982). We have confirmed these findings, further characterized the O-linked oligosaccharides and shown that 3H-palmitate is incorporated into one of the HSVl glycoproteins.…”
Section: Introductionmentioning
confidence: 99%